Soul treatment - Abdul Karim, Muhammad Shahrim (Universiti Putra Malaysia Press, 2015)
In this chapter various applications of birds will be explored. This chapter discusses birds in three main areas; food, therapy, and treatment. Birds of the same feathers flock together, is the most famous saying about birds.